2022
DOI: 10.3389/fchem.2022.834503
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Liquid Phase Separation in Nucleation Process of Biomineralization

Abstract: Biomineralization is a typical interdisciplinary subject attracting biologists, chemists, and geologists to figure out its potential mechanism. A mounting number of studies have revealed that the classical nucleation theory is not suitable for all nucleation process of biominerals, and phase-separated structures such as polymer-induced liquid precursors (PILPs) play essential roles in the non-classical nucleation processes. These structures are able to play diverse roles biologically or pathologically, and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 106 publications
(109 reference statements)
2
13
0
Order By: Relevance
“…These factors include surface wettability or inhomogeneity, which affect the nucleation barrier and the nucleation rate. Another difficulty stems from the interdisciplinary nature of this phenomenon, which has caused diversity in the terminology used by researchers from different fields [ 20 , 96 , 97 ].…”
Section: Calcium Carbonate Nucleation Processmentioning
confidence: 99%
See 3 more Smart Citations
“…These factors include surface wettability or inhomogeneity, which affect the nucleation barrier and the nucleation rate. Another difficulty stems from the interdisciplinary nature of this phenomenon, which has caused diversity in the terminology used by researchers from different fields [ 20 , 96 , 97 ].…”
Section: Calcium Carbonate Nucleation Processmentioning
confidence: 99%
“…Interestingly, recent studies increasingly use LLPS to explain the behaviour of calcium carbonate-containing solutions in the context of the mineralization mechanism [ 20 ]. Due to problems in determining the thermodynamics of the transient clusters that form during the nucleation process, molecular dynamics simulations were used to investigate the initial stability of the clusters with respect to the composition of the solution and formation pathway.…”
Section: Calcium Carbonate Nucleation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The ion precipitation from solutions onto hard surfaces and the formation of grains of sodium chloride are multifactorial mechanisms, which are still hypothetic [51]. Based on the results, it can be concluded that:…”
Section: Discussionmentioning
confidence: 98%